Salafi Islamic Education: Teaching Methods, Traditions and Ideologies in Lombok Boarding Schools: (Case study at Dar al-Qur'an and al-Hadith al-Majidiyyah al-Syafi'iyyah Institute in Nahdlatul Wathan Lombok) - Ulyan Nasri; Arif Mulyohadi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This research highlights the urgency of investigating teaching methods and curricula in Salafi educational institutions, specifically Ma'had Dar al-Qur'an and al-Hadith al-Majidiyyah al-Syafi'iyyah Nahdlatul Wathan Lombok. Despite the rapid development of modern curriculum and teaching methods, this institution maintains a traditional approach with seated learning and a classical curriculum. This study is a qualitative research focusing on literature and sources related to conventional Salafi education. The findings are as follows: Firstly, the institution's traditions persist, maintaining the study of classical Islamic texts through talaqqy or halaqah, teacher reverence, knowledge transmission, moral behavioral norms, and haflah. Secondly, the fundamental ideology is rooted in Islam, ahl al-Sunnah wa al-jama'ah, influenced by the theological thoughts of Imam Abu al-Hasan al-Asya'ri and Abu Mansur al-Maturidi in Aqeedah and the philosophical thoughts of Imam al-Ghazali and Imam Junaid al-Baghdadi in Sufism. Thirdly, the Institute's vision is to produce knowledgeable Islamic cadres proficient in the Quran, Hadith, and Salafusshalih texts. This research provides valuable insights into Salafi Islamic education in Lombok and its broader implications for education and society, enriching our understanding of the dynamics of Salafi Islamic education in a specific local context.